2019
DOI: 10.3390/en12152891
|View full text |Cite
|
Sign up to set email alerts
|

A Q-Cube Framework of Reinforcement Learning Algorithm for Continuous Double Auction among Microgrids

Abstract: Decision-making of microgrids in the condition of a dynamic uncertain bidding environment has always been a significant subject of interest in the context of energy markets. The emerging application of reinforcement learning algorithms in energy markets provides solutions to this problem. In this paper, we investigate the potential of applying a Q-learning algorithm into a continuous double auction mechanism. By choosing a global supply and demand relationship as states and considering both bidding price and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…[26], [27], [28] Artificial Neural Networks [11], [29], [30], [31], [32], [33], [34] [35], [12], [36], [37], [38], [39], [40] Reinforcement Learning [41], [42], [43], [44], [45] [46], [47], [48], [49], [50], [51], [52], [10], [53] Nature-Inspired Intelligence [54] [55]…”
Section: Overview Of Algorithmic Approaches For Electricity and Flexibility Tradingmentioning
confidence: 99%
See 2 more Smart Citations
“…[26], [27], [28] Artificial Neural Networks [11], [29], [30], [31], [32], [33], [34] [35], [12], [36], [37], [38], [39], [40] Reinforcement Learning [41], [42], [43], [44], [45] [46], [47], [48], [49], [50], [51], [52], [10], [53] Nature-Inspired Intelligence [54] [55]…”
Section: Overview Of Algorithmic Approaches For Electricity and Flexibility Tradingmentioning
confidence: 99%
“…Similarly, [34] propose a polynomial-time online learning algorithm for virtual trading on the day-ahead and the real-time electricity market. [30] propose a Q-learning approach for a double auction mechanism for trading between several micro-grid operators. Hence, the focus of this approach is more on bilateral trading rather than the application of trading strategies on a specific electricity market.…”
Section: Overview Of Algorithmic Approaches For Electricity and Flexibility Tradingmentioning
confidence: 99%
See 1 more Smart Citation
“…Batteries have been used in conjunction with reschedulable loads to perform the rescheduling to exploit time-of-use and real-time energy pricing schemes [34][35][36] and variable intraday electricity market prices [37]. Whereas most works are aimed at existing electricity markets, a few authors have demonstrated the benefits of RL to optimize the emerging decentralized electricity system on novel markets [38,39]. The above works involved decision-making on electricity markets, which is the most common type of RL application in this category.…”
mentioning
confidence: 99%
“…En la literatura se han presentado varios modelos y diseños basados en SD para abordar diferentes situaciones en entornos de licitación dinámica de mercados de comercialización de energía en micro-redes [10,17]. En algunos trabajos, se desarrollaron algoritmos de SD aplicables a micro-redes interconectadas, por ejemplo utilizando métodos de aprendizaje reforzado (reinforcement learning) [18].…”
unclassified